Autophagy regulation in preeclampsia: Pros and cons. (September 2017) - Nakashima, Akitoshi; Aoki, Aiko; Kusabiraki, Tae; Cheng, Shi-Bin; Sharma, Surendra; Saito, Shigeru
Highlights: Autophagy is an evolutionarily conserved process in eukaryotes to maintain cellular homeostasis against stress. Autophagy activation is observed in EVTs during early pregnant period in vivo, suggesting that EVTs use autophagy for adjusting to hypoxic and low-nutrient conditions. On the other hand, soluble endoglin inhibits autophagy in vitro, resulting in suppression of EVT functions. There are some opposing reports in which autophagy activation was more frequently observed in preeclamptic or FGR placentas than in normal pregnancy. It is still unknown how autophagy contributes to pathophysiology of preeclampsia. This review introduces the role of autophagy for maintaining pregnancy and its correlation with preeclampsia. Abstract: Autophagy is an evolutionarily conserved process in eukaryotes to maintain cellular homeostasis against stress. This process has two main functions: producing energy and quality control of intracellular proteins. During early pregnancy, extravillous trophoblasts (EVTs) invade the uterine myometrium and migrate along the lumina of spiral arterioles under hypoxic and low-nutrient conditions. Autophagy activation is observed in EVTs under these conditions, suggesting that EVTs use autophagy for adjusting to such harsh conditions. On the other hand, soluble endoglin, which is increased in sera in preeclamptic cases, inhibits autophagy in vitro, resulting in suppression of EVT functions, invasion and vascular remodeling. In addition, p62/SQSTM1, a substrate degraded by autophagy, accumulates in EVTs in preeclamptic placental biopsy samples, exhibiting impaired autophagy in vivo . There are, however, some opposing reports in which autophagy activation, an increase of autophagy vacuoles or LC3 dots, was more frequently observed in preeclamptic or FGR placentas than in normal pregnancy. Thus, changes in autophagy status are seen in preeclamptic placentas, but the mechanism by which autophagy modulates biological changes in the placentas is still unknown. Recently, there is increasing evidence that autophagy is involved in maintaining pregnancy. This review introduces the role of autophagy for maintaining pregnancy and its correlation with preeclampsia.